2019
DOI: 10.16952/pns.2019.16.2.55
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between Terminal Care Stress and Knowledge and Perception of Hospice-Palliative Care among Pediatric Nurses

Abstract: Purpose: This study examined the knowledge and perception of hospice-palliative care and terminal care stress among pediatric nurses, and the relationships among these variables. Methods: In this descriptive research study, 154 pediatric nurses who experienced terminal care at least once were surveyed. This study used three scales, including the Palliative Care Quiz for Nursing (PCQN), Perception of Hospice-Palliative Care, and Terminal care stress. Data analyses using SPSS 22.0 included descriptive statistics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In other words, since ANCD and NC interact, even if ANCD is low, NC buffers and improves the performance of terminal care. A previous study explored the factors influencing the performance of terminal care among intensive care unit nurses and found that stress during end-of-life nursing [ 8 ] and the stress associated with end-of-life nursing can be caused by negative attitudes or burdens of the patient or caregiver toward hospice care, interpersonal problems, or lack of knowledge and perception of hospice care [ 8 , 24 , 25 ]. Thus, even if nurses have a positive attitude toward nursing care of the dying, it is difficult for their attitudes to lead to enhanced performance unless they establish a trusting relationship with the patient’s family.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, since ANCD and NC interact, even if ANCD is low, NC buffers and improves the performance of terminal care. A previous study explored the factors influencing the performance of terminal care among intensive care unit nurses and found that stress during end-of-life nursing [ 8 ] and the stress associated with end-of-life nursing can be caused by negative attitudes or burdens of the patient or caregiver toward hospice care, interpersonal problems, or lack of knowledge and perception of hospice care [ 8 , 24 , 25 ]. Thus, even if nurses have a positive attitude toward nursing care of the dying, it is difficult for their attitudes to lead to enhanced performance unless they establish a trusting relationship with the patient’s family.…”
Section: Discussionmentioning
confidence: 99%